Bioprocessing of Avian Influenza VLP Vaccine using Baculovirus-Insect Cell Expression System - Chrisdianto, Matthew; Damai, Fedric Intan; Mulyono, Roselyn; Virginia, Jesslyn Audrey; K, Katherine (Indonesia International Institute for Life Sciences, 2022)
Vaccines are widely used as a preventive measure against influenza virus infection. However, these vaccines gain concerns regarding their biosafety due to implementing the highly pathogenic avian influenza in the production process. A breakthrough that uses insect cells due to their ability to produce protein rapidly, especially viral antigens for the potential avian influenza outbreak, is being extensively researched. Insect cells infected by baculovirus (BV) are utilized to express proteins known as virus-like protein (VLP). The objective of this review is to assess the production of the avian influenza vaccine (i.e., H5N1 and H7N9 strains) made from VLP by utilizing a baculovirus-insect cell (BV-IC) expression system. A narrative review was conducted by screening international indexed journals from the last 10 years about the topic. The result shows that VLP vaccine development using BV-IC expression can be a cheaper and safer alternative to conventional vaccines while also producing a high yield. The upstream process consists of the IC infection by the BV and BV-IC cell cultivation inside the bioreactor. The downstream process consists of the purification of the VLP product until it becomes a functioning vaccine. The VLP vaccine has improved immunogenic quality, enabling a more specific immune response than other vaccines. However, studies performed on avian influenza vaccines produced by the BV-IC expression system are still lacking. Therefore, further studies are required to improve the current VLP vaccine production processes.